The mouse olfactory receptor gene family - Godfrey, Paul A. (National Academy of Sciences, 2004)
In mammals, odor detection in the nose is mediated by a diverse family of olfactory receptors (ORs), which are used combinatorially to detect different odorants and encode their identities. The OR family can be divided into subfamilies whose members are highly related and are likely to recognize structurally related odorants. To gain further insight into the mechanisms underlying odor detection, we analyzed the mouse OR gene family. Exhaustive searches of a mouse genome database identified 913 intact OR genes and 296 OR pseudogenes. These genes were localized to 51 different loci on 17 chromosomes. Sequence comparisons showed that the mouse OR family contains 241 subfamilies. Subfamily sizes vary extensively, suggesting that some classes of odorants may be more easily detected or discriminated than others. Determination of subfamilies that contain ORs with identified ligands allowed tentative functional predictions for 19 subfamilies. Analysis of the chromosomal locations of members of each subfamily showed that many OR gene loci encode only one or a few subfamilies. Furthermore, most subfamilies are encoded by a single locus, suggesting that different loci may encode receptors for different types of odorant structural features. Comparison of human and mouse OR subfamilies showed that the two species have many, but not all, subfamilies in common. However, mouse subfamilies are usually larger than their human counterparts. This finding suggests that humans and mice recognize many of the same odorant structural motifs, but mice may be superior in odor sensitivity and discrimination.